Biosafety and Biosecurity Measures in Clinical/Research Laboratory: Assistance with International Guidelines: Laboratory Biosafety and Biosecurity Guidelines - Kalam, Adil; Asif, Ehtisham; Tabassum, Saiqa (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
Nowadays, laboratory biosafety and biosecurity are serious global issues in clinical laboratories and academic research labs. With the high rate of biological harm caused by evolving infectious diseases and bioterrorism, we all are equally responsible for biosafety and biosecurity at the workplace, but it is the main responsibility of governments from all over the world that must raise their awareness and preparedness for detecting and containing hazardous biological agents, this responsibility includes not only providing a biological safe environment for laboratory workers and also biosafety of others in the institution and community. Safe and effective laboratory operations and pathogen handling determine the safety of the laboratory workers, pathogens, and the laboratory environment, these all are the important variables in the successful performance of laboratory assays. The basic concepts of laboratory management, laboratory biosafety, and laboratory biosecurity are addressed in this article. In addition, DURC (dual-use research of concern) is the research that is commenced for lawful reasons that produce knowledge, information, technology, and/ or products that can be used for both good and bad aspects. Biosafety and biosecurity measures should be included in the laboratory policy manuals for the guidance of laboratory personnel.